Prevalence and self-perceived experiences with the use of hormonal contraceptives among competitive female cross-country skiers and biathletes in norway: the FENDURA project - Engseth, T. P.; Andersson, E. P.; Solli, G. S.; Morseth, B.; Thomassen, T. O.; Noordhof, D. A.; Sandbakk, O.; Welde, B. (Frontiers in Sports and Active Living, 2022)
Purpose: To investigate the prevalence of hormonal contraceptive (HC) use by female cross-country (XC) skiers and biathletes competing at a national and/or international level, their reasons for HC use, and to compare negative symptoms related to the HC-/menstrual cycle in HC users and non-HC users. Additionally, to characterize the self-perceived influence of HC use on training and performance.